If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7(7 + -1x) = 3 3x + (7 * -7 + -1x * -7) = 3 3x + (-49 + 7x) = 3 Reorder the terms: -49 + 3x + 7x = 3 Combine like terms: 3x + 7x = 10x -49 + 10x = 3 Solving -49 + 10x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + 10x = 3 + 49 Combine like terms: -49 + 49 = 0 0 + 10x = 3 + 49 10x = 3 + 49 Combine like terms: 3 + 49 = 52 10x = 52 Divide each side by '10'. x = 5.2 Simplifying x = 5.2
| lots=0.4 | | 7(u-2)-5u=-26 | | 7w+5(w+5)=-35 | | 35=2(v-5)+3v | | 5x+1(x^2-6x+11)= | | 15x-3xy-y+5=0 | | -1.09375=ln(0.1/x) | | 2x²-6x-36/2x-12 | | Y=4x+-20 | | 4x^2+5y^2-8x+20y=-25 | | 0.017=-0.005889*ln(1/x) | | 40+0.6x=x | | -6x=d+4 | | (x-3y)(3x+11y)= | | (1-8r)(1+8r)= | | X/-4=3.45 | | X^2-4.9x+2.9=0 | | (5+3i)(5-3i)=34 | | 6(x+1.1)=5x+8.1 | | 0.6x+40=x | | cos(3x)+cos(2x)-cos(x)=0 | | X^2-4.8x+2.7=0 | | (X-5-3i)(x-5+3i)=34 | | 10x-2x=0 | | 4/21-8/45 | | f(a-2)=x^2+4x+3 | | 3x^2+29x-5.7=0 | | 4x*6x-3x*9x= | | f(x)=ln(x^7-10/x) | | 5/9-1/3•1/6 | | 24x^2-7x^3=19 | | (x^2+8x-4)-(7x+5)=x^2-8 |